Strengthening rural livelihoods in the face of rapid urbanisation in Africa: Reader for Brussels Briefing 48 - Boto, Isolina; Mofolo, Lebo (Technical Centre for Agricultural and Rural Cooperation, 2017)
Globalization and urbanization have transformed economies and social systems in countries around the world in the past decades. The information in this document was compiled as background reading material for the 48th Brussels Development Briefing on Strengthening rural livelihoods in the face of rapid urbanisation in Africa co-organised by CTA, BMZ/GIZ, ACP Secretariat, European Commission (DG DEVCO) and Concord.